Mechanical properties of oil palm frond wood filled thermoplastic polyurethane - Lubis, Abdul Munir Hidayat Syah; Abd Razak, Jeefferie; Muhamad Damanhuri, Amir Abdullah; Ab Razak, Muhammad Nur Asyraf; Rahmah, Anisa Ur (Universiti Malaysia Perlis, 2020)
The problem of the biomass waste produced from palm oil plantation is present today. The biomass waste typically is sourced from oil palm trunk (OPT), oil palm frond (OPF) and oil palm fruit bunch. Considering the huge amounts OPF wood waste from palm oil plantation, the waste can have other added value if they can be used as in polymer composite materials. This study is subjected to investigate the effect of oil palm frond (OPF) fiber and powder loading to hardness, toughness, tensile and flexural strength of thermoplastic polyurethane (TPU) as wood polymer composite. Frond fiber with size of 2-3 mm and frond powder with size of 60-90 micron were used as filler materials. The TPU/OPF composite samples were fabricated by compressive molding approach. The result shows that hardness of TPU based composite increased by 48% with the addition of 30 wt.% of OPF powder. Ultimate tensile strength of TPU increased by 26% with addition of 30 wt.% OPF frond powder. The impact strength of TPU increased by about 50 % by the addition of 30 wt.% of OPF frond fiber, while the flexural strength of TPU/OPF composites increased by about 86% by the addition of 30% OPF frond fiber. The microstructure of TPU/OPF composite samples shows good interfacial bonding between TPU matrix to OPF powder and OPF fiber, which represents a significant improvement of mechanical properties of TPU/OPF composites. It can be concluded that both, OPF powder and fiber addition significantly improved the mechanical properties of TPU. The OPF powder improved hardness and tensile strength, while the OPF fiber improved on the impact and flexural strength of the TPU